Eradication of hepatitis C virus infection in thalassemia patients in Iran using various treatment strategies - Meisam Moghimbeygi; Seyed Moayed Alavian (Elsevier, 2020)
Background: Chronic hepatitis C virus (HCV) infection is considered as one of the leading causes of liver disease in thalassemic patients in Iran. Over 40% of the mortality in these patients is related to HCV. Objectives: The present study aimed at estimating HCV prevalence in thalassemic patients in Iran and to determine the number of infections until eradication is achieved. Methods: A meta-analysis approach was used to estimate the number of HCV-infected thalassemic patients in the country. The prevalence rate was measured using a modeling approach to predict the number of cases until eradication using several scenarios in terms of testing and treatment, in particular the use of direct acting antiviral drugs (DAAs). Results: With the advent of DAAs with a high rate of treatment success, HCV could be eradicated earlier than originally thought among this group of patients. Based on previous predictions the number of HCV-infected thalassemic patients would have been below 66 by 2020. However, according to our predictions, the number will be less than 10 when using DAAs. Conclusion: We believe that HCV eradication can be achieved in thalassemic patients with an increased life expectancy by funding DAA-based new treatment strategies. This has been exemplified in Alborz, Lorestan, and South Khorasan provinces with HCV eradication in this group of patients.